2011
DOI: 10.1186/gb-2011-12-7-r70
|View full text |Cite
|
Sign up to set email alerts
|

Extensive characterization of NF-κB binding uncovers non-canonical motifs and advances the interpretation of genetic functional traits

Abstract: BackgroundGenetic studies have provided ample evidence of the influence of non-coding DNA polymorphisms on trait variance, particularly those occurring within transcription factor binding sites. Protein binding microarrays and other platforms that can map these sites with great precision have enhanced our understanding of how a single nucleotide polymorphism can alter binding potential within an in vitro setting, allowing for greater predictive capability of its effect on a transcription factor binding site.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
125
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 48 publications
5
125
0
1
Order By: Relevance
“…The promoter region of human miR-21 is located ϳ(-)3.5 kb upstream of the pre-miR-21 sequence (32). We found that the corresponding region in the rat miR-21 locus is located at the ϳ(-)2.6 kb region and contains a conserved putative NF-B binding motif (GGR(A/G)R(A/G)NNY(C/ T)Y(C/T)C) (33) (Fig. 4C, upper panel).…”
Section: Pkci-maintained Rescs Express a Reduced Amount Of Trophoblasmentioning
confidence: 99%
“…The promoter region of human miR-21 is located ϳ(-)3.5 kb upstream of the pre-miR-21 sequence (32). We found that the corresponding region in the rat miR-21 locus is located at the ϳ(-)2.6 kb region and contains a conserved putative NF-B binding motif (GGR(A/G)R(A/G)NNY(C/ T)Y(C/T)C) (33) (Fig. 4C, upper panel).…”
Section: Pkci-maintained Rescs Express a Reduced Amount Of Trophoblasmentioning
confidence: 99%
“…Compared to those methods Spec-seq has one significant disadvantage, but several valuable advantages. The disadvantage is that the number of sequences that can be assayed in a single experiment is in the thousands (but see alternative below), whereas PBM and related methods (Berger et al 2006;Warren et al 2006;Nutiu et al 2011), SELEX-seq (Zhao et al 2009;Zykovich et al 2009;Jolma et al 2010Jolma et al , 2013Wong et al 2011), andB1H (Meng et al 2005;Christensen et al 2011;Gupta et al 2014) can assay millions, or more, of sequences simultaneously. But those methods do not measure binding affinity directly, but rather something related to it such as binding site counts in SELEX-seq and B1H or fluorescence intensity in PBM.…”
Section: Lac Repressor Specificitymentioning
confidence: 99%
“…Measurements of affinity changes due to operator sequence variation, by base replacement, by the use of base analogs, or by changing the length of the operator, have been performed almost since the operator sequence was first determined (Goeddel et al 1978;Sadler et al 1983;Betz et al 1986;Sartorius et al 1989;Lehming et al 1990;Sasmor and Betz 1990;Frank et al 1997;Spronk et al 1999;Falcon and Matthews 2001;Kalodimos et al 2002Kalodimos et al , 2004bDaber and Lewis 2009). But those analyses all measured binding affinity to only a few sequences.The lac repressor has not, to our knowledge, been analyzed by current high-throughput methods that can determine specificity over thousands, or even millions, of sequences in parallel (Stormo and Zhao 2010), such as protein-binding microarrays (PBM) (Berger et al 2006;Gordan et al 2013), SELEX-seq [or HT-SELEX (Zhao et al 2009;Zykovich et al 2009;Jolma et al 2010;Wong et al 2011)], bacterial one-hybrid (B1H) (Meng et al 2005;Noyes et al 2008;Christensen et al 2011), and mechanically induced trapping of molecular interactions (MITOMI) (Maerkl and Quake 2007). While those methods offer an expansive overview of binding specificity, the accuracies of the resulting models are highly variable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies that aim to address this gap employed in vitro-based methods (e.g., DIP-seq [Liu et al 2006], PB-seq [Guertin et al 2012], gcPBM Wong et al 2011;Gordan et al 2013], EMSA-seq [Wong et al 2011], SELEXseq [Slattery et al 2011;Jolma et al 2013], MITOMI [Maerkl and Quake 2007;Fordyce et al 2010], HiTS-FLIP [Nutiu et al 2011]) and identified various mechanisms that affect TF binding, including chromatin accessibility (Liu et al 2006;Guertin et al 2012), cofactors that influence binding specificity Slattery et al 2011), TF dimer interactions (Wong et al 2011;Jolma et al 2013), and the effect of sequences flanking the core TF binding site (TFBS) (Maerkl and Quake 2007;Nutiu et al 2011;Gordan et al 2013;Jolma et al 2013;Rajkumar et al 2013) that can be mediated through DNA shape.…”
mentioning
confidence: 99%